Dynamic Contracts and Learning by Doing - Julien Prat (Institute for the Study of Labor (IZA), 2014)
This paper studies the design of optimal contracts in dynamic environments where agents learn by doing. We derive a condition under which contracts are fully incentive compatible. A closed-form solution is obtained when agents have CARA utility. It shows that human capital accumulation strengthens the power of incentives and allows the principal to provide the agent with better insurance against transitory risks.
Keywords: D82; D83; J24; J41; 330; human capital; principal agent problem; moral hazard